A requirement of dendritic cell-derived interleukin-27 for the tumor infiltration of regulatory T cells. Issue 5 (17th January 2014) - Xia, Siyuan; Wei, Jun; Wang, Jingya; Sun, Huayan; Zheng, Wenting; Li, Yangguang; Sun, Yanbo; Zhao, Huiyuan; Zhang, Song; Wen, Ti; Zhou, Xinglong; Gao, Jian-Xin; et al.
Abstract : IL-27 promotes immunosuppressive Treg recruitment into tumors, by inducing dendritic cell derived CCL22 production. ABSTRACT: Tregs (Foxp3 + CD4 + ) are enriched in tumors to foster a tolerant microenvironment that inhibits antitumor immune response. IL-27 is reported to regulate the development and function of Tregs in vitro and in vivo; however, the effects of endogenous IL-27 on Tregs in the tumor microenvironment remain elusive. We demonstrated that in the absence of DC-derived IL-27, Tregs were decreased significantly in transplanted B16 melanoma, transplanted EL-4 lymphoma, and MCA-induced fibrosarcoma by using IL-27p28 conditional KO mice. Further studies revealed that IL-27 promoted the expression of CCL22, which is established to mediate the recruitment of peripheral Tregs into tumors. Tumor-associated DCs were identified as the major source of CCL22 in tumor sites, and IL-27 could induce CCL22 expression in an IL-27R-dependent manner. Intratumoral reconstitution of rmCCL22 or rmIL-27, but not rmIL-27p28, significantly restored the tumor infiltration of Tregs in IL-27p28 KO mice. Correlated with a decreased number of Tregs, tumor-infiltrating CD4 T cells were found to produce much more IFN-γ in IL-27p28 KO mice, which highlighted the physiological importance of Tregs in suppressing an antitumor immune response. Overall, our results identified a novel mechanism of action of IL-27 on Tregs in the context of cancers.